Semiotic Analysis of John Fiske: The Meaning of the Song "Senja Kala Itu" by Gading Suryadmaja - Suryadmaja, Galih (Jurnal Multidisiplin Sahombu, 2025)
The song "Senja Kala Itu" by Gading Suryadmaja, featured in the album Terlahir Kembali, evokes a nostalgic sentiment surrounding childhood experiences, particularly the relationship between a child and a father. This study aims to uncover the symbolic meanings embedded in the song through a semiotic approach, as proposed by John Fiske. Fiske, renowned for his semiotic theory emphasizing the production of meaning through texts and social contexts, serves as the analytical framework for examining the song’s lyrics. In this analysis, "Senja Kala Itu" is viewed as a text rich in signifiers representing memories and implicit emotions. A qualitative approach is employed, utilizing semiotic analysis based on Fiske’s theory. The analysis of the lyrics, which depict the twilight atmosphere of childhood, identifies symbols such as twilight, roads, and the notion of 'home,' each carrying dual meanings in both social and personal contexts. Twilight, symbolizing the passage of time, becomes a metaphor for longing and nostalgia for a past that cannot be reclaimed. The father’s role as an authority figure and reminder of time, as depicted in the song’s lyrics, reflects a relationship characterized by affection, yet also by a sense of obligation. The portrayal of the father’s command to return home, coupled with the yearning for the past, constructs a broader narrative on childhood experiences, temporal boundaries, and personal growth. The findings of this study reveal that the song transcends mere nostalgia for childhood; it conveys messages about time, responsibility, and power relations within the family. By applying Fiske’s semiotic theory, this analysis demonstrates how the signs within the song’s lyrics function to construct meaning, reflecting social dynamics and offering a new understanding of generational and temporal relationships.